1997
DOI: 10.1046/j.1365-2567.1997.d01-2249.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the antigen‐presenting capabilities of class II MHC‐expressing human lung epithelial and endothelial cells

Abstract: SUMMARYHuman lung alveolar epithelial cells constitutively express class II major histocompatibility complex ( MHC). Human lung microvascular endothelial and small airway epithelial cells can be induced to express class II MHC by stimulation with the pro-inflammatory cytokine interferonc. The levels of class II MHC on lung epithelial and endothelial cells were comparable to those seen on an Epstein-Barr virus (EBV )-transformed B-cell line. However, the costimulatory molecules B7-1 and B7-2 were not expressed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
81
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 28 publications
4
81
0
4
Order By: Relevance
“…Indeed, in several studies, T cells exposed to IFN-␥-treated epithelial cells became unresponsive to the same HLA Ags presented by professional APC. For example, Frasca et al (12) and Singer et al (39) showed that kidney epithelial cells could induce nonresponsiveness in peripheral CD4 ϩ T cells, while Cunningham et al (11) described a similar phenomenon using lung epithelial cells and Marelli-Berg et al (13) reported similar findings with a thyroid epithelial cell line. This group also showed that at least one of the mechanisms by which epithelial cells are able to induce nonresponsiveness is via Fas (CD95)-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Indeed, in several studies, T cells exposed to IFN-␥-treated epithelial cells became unresponsive to the same HLA Ags presented by professional APC. For example, Frasca et al (12) and Singer et al (39) showed that kidney epithelial cells could induce nonresponsiveness in peripheral CD4 ϩ T cells, while Cunningham et al (11) described a similar phenomenon using lung epithelial cells and Marelli-Berg et al (13) reported similar findings with a thyroid epithelial cell line. This group also showed that at least one of the mechanisms by which epithelial cells are able to induce nonresponsiveness is via Fas (CD95)-mediated apoptosis.…”
Section: Discussionmentioning
confidence: 92%
“…There is a broad agreement that HLA class II-positive endothelial cells (5,6,16,28,29), but not epithelial cells (7,(11)(12)(13)(14)30), fibroblasts (31,32), or smooth muscle cells (28,33), cause alloproliferation of resting CD4 ϩ T cells. The advantage of CIITA transfection is that it can cause up-regulation of HLA-class II molecules without the pleiotropic effects of IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations